Determinação da influência do aditivo superplastificante no desempenho de um concreto estrutural autoadensável de resistência de 40 MPa - Sandra Moreira Fernandes Teixeira (2014)
Self-compacting concrete is a composite with rheological properties that make it a very attractive material for casting homogeneous and long lasting pieces. Its usage allows for an increased productivity rate, environmental gains and larger articles. Hence, this type of concrete has been being used increasingly in the global market. Its performance depends on the nature and ratio of its constituents and the influence of superplasticizers has been widely studied. However, that performance is usually assessed by comparing self-compacting concrete with a reference concrete with the same mechanical resistance to compression but made of different mortar and water/cement ratios. Therefore, the study of the influence of superplasticizers is jeopardized by disparities in material composition. Aiming to isolate the superplasticizers influence, in the present study, the performances of both conventional and self-compacting concrete samples of 40 MPa, composed of the same local materials found in Minas Gerais, same water/cement ratio and same mortar rate were analyzed. The composites characteristics were evaluated, both at fresh and solid states, regarding workability, incorporated air, mechanical resistance, elasticity modulus and deterioration rate and the results point to the superplasticizer, by itself, not directly influencing the performance of the concrete in its consolidated state.